Generation and characterisation of mesenchymal stem cells derived from human cartilage - Sandrasaigaran, Pratheep (2014)
Mesenchymal stem cells (MSCs) were initially discovered as stromal cells that possess unique characteristics as compared to other counterparts of multipotent stem cells. Besides the capability of self-renewal and differentiating into a variety of mature cells, MSCs also exert potent immuno-regulatory activities on various immune cells. This exclusive characteristic has enabled MSCs to be recognised as an ideal cell based treatment in the field of regenerative medicine, gene therapy and immunotherapy. As regeneration of cartilage tissue in situ is hampered by limited intrinsic growth, this study explores the feasibility of generating human MSCs from sports injured patients‟ cartilages and investigates the possibility to differentiate them into cartilage tissues. For this, MSCs were generated from tissues that was harvested from a non-weight bearing region of cartilage during an arthroscopy procedure and characterised based on morphology, immunophenotype and immunomodulatory properties. Furthermore, the MSCs generated from their original physiognomy (cartilage) are believed to support the cartilage regeneration much greater. The cartilage tissues in laboratory were subject to enzymatic digestions and cultured in plastic culture ware. A series of experiments were designed using the cells from passage three onwards. Initially, the cells were cultured at 200 cells/cm2 and harvested at day 10 and 12 respectively to determine the cells‟ growth kinetics and population doubling time. Cells generated from these tissues showed spindleshaped fibroblast morphology with a population doubling time of approximately 27 hours. Next, the cells were then stained with respective antibodies with fluorescent conjugated markers and analysed in flow cytometer. When the right cells‟ populations were gated, a common surface markers that are related to mesenchymal origin however not haematopoietic were observed (CD29+, CD73+, CD90+, CD105+, HLA-ABC+, CD271-, CD14 , CD19-, CD45-, CD86-, CD80-, CD34- and HLA-DR-). Besides that, these cells were also subjected to the cell differentiation analysis. The cells were allowed to confluent before cultured with the respective differentiation media according to the manufacturer‟s instructions. Cells‟ cytostaining assay and PCR analysis on isolated total RNA showed the cells are capable of differentiating into mesodermal lineages (chondrocytes, adipocytes and osteocytes). In term of stemness, human cartilage derived cells expressed the early embryonic markers of SOX2, REX1, OCT4, NANOG; hence indicating their inherent pluripotency. Such results has confirmed cartilage tissues hold the aptitude to generate mesenchymal stem cells and these cells were termed as human cartilage derived mesenchymal stem cells (hC-MSCs). Further experiments reveal that the hC-MSCs are able to suppress proliferation of activated T-lymphocytes, demonstrating that their immunomodulatory effects are analogous to bone marrow derived MSCs. In the presence of hC-MSCs, the proliferation of the T cells was severely inhibited in dose dependent manner but their activation profile was well preserved. They further affirm the requirement for the cell-to-cell contact during their immuno-inhibitory activity. These outcomes were confirmed in the hC-MSCs: T cells co-culture assay and further analysis of CD25 expressions by activated T cells shows no variations when they were cultured either with or without the presence of hC-MSCs. Furthermore when the activated T cells were co-cultured with hC-MSCs, the immune cells were arrested in G0/G1 phase of the cell cycles and their commitments into S phase were not permissible. Based on the acquired laboratory data, it has been shown that human cartilage sample could serve as a good source to generate mesenchymal stem cells and the functional properties of human cartilage mesenchymal stem cells in term of differentiating into mature chondrocytes plus ability to prevent the expansion of activated T cells has endeavoured as a new paradigm to treat destructive autoimmune diseases of joints such as rheumatoid arthritis. Moreover, this study has further strengthened the fundamental findings on human cartilage mesenchymal stem cells biology, thus adding value to the existing clinical therapy.